Electrochemical performance of Mo doped high voltage spinel cathode material for lithium-ion battery - Kazda, T. (2018)
This article deals with the properties of high-voltage cathode material LiNi0.5Mn1.5O4 synthesized by a solid-state reaction method and the influence of doping this material by molybdenum. The samples – LiMox+ yNi0.5 - xMn1.5 - yO4 with different Mo contents (x = 0.00, 0.05, y = 0.00, 0.05) were successfully synthesized by two step annealing process and they were then investigated by SEM, EDS spectroscopy, thermo gravimetric analysis, cyclic voltammetry and charge–discharge tests at different loads and high temperature in lithium-ion cells with metal lithium as a counter electrode. Results showed that the initial discharge capacity and capacity during high temperature cycling of the LiMox + yNi0.5 - xMn1.5 - yO4 cathode were improved with addition of Mo when x = 0.05. Thermal analysis results suggested that the Mo doping slightly improved the stability of the crystal structure of the LiNi0.5Mn1.5O4 cathode which leads to an improved stability during high temperature galvanostatic cycling.